The Occupational Stress Level of Employees in the Penitentiary Class II A, Magelang - Lestari, Veranika Dwi; Azzahra, Fatimah; Faizah, Rayinda (Journal of Islamic Communication and Counseling, 2024)
The life of an employee entails demands and work conditions that are part of an individual's existence alongside occupational or work-related stress. Work-related stress arises from an individual's response to high workloads and job demands. This study aims to delve deeper into work-related stress among Penitentiary Class II A employees in Magelang City. The research employs a descriptive qualitative approach with three participants as informants using snowball sampling. The criteria for this research include prison officers of Penitentiary Class II A in Magelang, aged between 18 to 65 years old, and experienced in working at the institution. The findings of this study indicate that all three informants experience work-related stress in their work environments. Work stress varies and is driven by factors such as cognitive appraisal, experience, demands, interpersonal influence, and the stress condition viewed from individual experiences (work conditions, personality, emotions, gratitude, and hobbies).